A model for sharing knowledge in architectural firms. Issue 2 (2014) - Joseph Bashouri; Glen William Duncan
<x xml:space="preserve"> Abstract </x> Purpose – This theoretical paper aims to develop a model of how best to facilitate projects knowledge sharing within architectural firms to learn from lessons and improve the firm innovation capabilities, knowledge and skills. Design/methodology/approach – A conceptual framework is developed by reviewing the literature in the fields of knowledge management (KM), the project‐based organisation and communities of practice (CoPs) and linking these to the literature on the architectural firm. Findings – In the architectural firm, KM strategy needs to be linked to the overall business strategy determining the balance of codification/personalisation. The firm needs to be structured as a double‐knit organisation connecting projects with CoPs. This structure creates a social network that allows sharing the useful and innovative knowledge created through the design process. Success depends on building a knowledge environment, providing organisational support and building a learning architecture within projects. A balanced combination of information and communication technologies, lessons‐learned, storytelling, conversational learning and dialogue are needed as knowledge sharing methods. Originality/value – This paper's originality is in constructing a conceptual framework or model for knowledge sharing within the architectural firm with CoPs at the heart of that model. This paper is valuable to any architectural practice that aims to protect its reputation, improve its performance and increase its innovative knowledge base. It is also valuable to the construction industry by helping to minimise design mistakes and the consequent cost of construction rework.